Gênero, uma palavra (mal)dita: usos e apropriações de uma categoria analítica dentro e fora da academia - Vasconcelos, Francis Emmanuelle Alves (2019)
Gender is an analytical and political category forged by the articulation between social movements and Academia from the second half of the twentieth century, in a tense relationship between the two. These tensions are reintroduced in a deeply transformed way from the beginning of the second decade of the twenty-first century in Brazilian society. Feminism and gender have become (bad) words. Damn because distorted, still, said. Never before in Brazilian history has it been talked about so much about it: books, social networks, websites, politics and right-wing movements. There is a wave of conservatism in Brazil, and part of it has undeniably turned against feminism and what they call "gender ideology." We sought to understand these conflicts. The time frame of the research was between the years 2014 and 2018. We sought to understand, initially, the reflexes that the gender readings have in the life of the gender researchers. For this, interviews with gender researchers were carried out. Secondly, we sought to understand the antifeminist discourses from a vast bibliographical research of antigenic and antifeminist productions, interviews and systematic observations with leaders of right-wing groups and in their meetings promoted in Fortaleza. We identify the following nodes of the conflict: equality, since the idea that women are wanting to be men and women is widespread. Hence the apocalyptic tone that surrounds this discourse, because, as a result of this persecuted equality, humanity would be doomed to the end. Other points of tension: abortion, from strong emotional appeal of protection to life, are reflected in bills that undermine the reproductive rights of women. In addition, conflicts with religions and the spread of the idea of "gender ideology" from there. The hate speech against feminism is one of the front lines of the conservative wave in Brazil that attacks all left-wing ideologies in order to gain space in the country's political power. It has served as political currency and garnered many votes, having led many legislators to the Legislative Houses by Brazil in the last elections. More than understanding these discourses, it remains to seek strategies to face them: in the micro-everyday spaces of family, friends, social networks and in the macro spaces of social movements.